Investigation of the relationship between isokinetic lower extremity strength and the vertical jump parameter in elite women football players - Soyal, M.; Aksoy, Ö.; Sengöl, O.; Kiliç, S. (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim. It can be said that recently, with the popularity of women's football and playing at a professional level, physical and physiological needs have increased. In this context, this study was conducted to examine the relationship between isokinetic lower extremity strength and vertical jump parameters in elite female football players.